BRIGHT, DARK, AND SINGULAR OPTICAL SOLITON SOLUTIONS FOR PERTURBED GERDJIKOV-IVANOV EQUATION - Ulutas, Esma; İnç, Mustafa; Baleanu, Dumitru; Kumar, Sunil (Vinca Inst Nuclear Sci, 2021)
This study consider Gerdjikov-Ivanov equation where the perturbation terms appear with full non-linearity. The Jacobi elliptic function ansatz method is implemented to obtain exact solutions of this equation that models pulse dynamics in optical fibers. It is retrieved some bright, dark optical and singular solitons profile in the limiting cases of the Jacobi elliptic functions. The constraint conditions depending on the parameters for the existence of solitons are also presented.
Keywords: Jacobi elliptic functions; optical solitons; Gerdjikov-Ivanov equation